RESEARCH OF POWER CHARACTERISTICS OF SEMICONDUCTOR CONTOUR DETECTOR - Margaryan, R. Kh.; Ohanyan, K. S.; Petrosyan, L. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
Our research shows that semiconductor detectors with contour electrode have excellent energy resolutions 0.8% and linear characteristics. Therefore, detectors with such configurations of electrodes can be used in alpha spectroscopy. Detectors with contour electrode allow decreasing the energy threshold of registered particles in contrast to traditional detectors.